PENERBITAN BANK GARANSI PADA LEMBAGA PERBANKAN MENURUT UU NO. 10 TAHUN 1998 - Kornelis Kornelis (Universitas 17 Agustus 1945 Samarinda, 2015)
ABSTRACT Factors that lead to bad credit, influenced by: Factors that are intertnal, namely: Misuse of credit; The low level of education; The characters are not good; Financial difficulties. External factors, which is derived from the circumstances that happen beyond the reach ability of the debtor or circumstances that force (coercion) as a state of unstable economy.Party Regional Development Bank Samarinda in making efforts to overcome bad credit, among others: Peace; Billing through legal channels. Completion of credit to BUPLN (Auction Receivables Affairs Agency); Submitted an application to the District Court to hold a foreclosure.